Who is predisposed to insomnia: A review of familial aggregation, stress-reactivity, personality and coping style - Harvey, Christopher-James; Gehrman, Phil; Espie, Colin A. (Sleep medicine reviews, 2014)
Insomnia is a common health complaint world-wide. Insomnia is a risk factor in the development of other psychological and physiological disorders. Therefore understanding the mechanisms which predispose an individual to developing insomnia has great transdiagnostic value. However, whilst it is largely accepted that a vulnerable phenotype exists there is a lack of research which aims to systematically assess the make-up of this phenotype. This review outlines the research to-date, considering familial aggregation and the genetics and psychology of stress-reactivity. A model will be presented in which negative affect (neuroticism) and genetics (5HTTLPR) are argued to lead to disrupted sleep via an increase in stress-reactivity, and further that the interaction of these variables leads to an increase in learned negative associations, which further increase the likelihood of poor sleep and the development of insomnia.